2006
DOI: 10.1097/01.tp.0000233870.54297.9a
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Indefinite Survival of Fully Mismatched Cardiac Allografts and Generation of Regulatory Cells by Sarpogrelate Hydrochloride

Abstract: SH induced indefinite survival of fully allogeneic cardiac allografts, generated CD4 regulatory cells, inhibited ICAM-1 expression in the allografts, and upregulated IL-4 and IL-10 production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
(34 reference statements)
1
13
0
Order By: Relevance
“…Inoue et al (2011) [17] showed that a 5-HT 2A agonist enhanced Concavalin-A induced activation whereas a 5-HT 2A antagonist blocked T-cell receptor mediated interleukin-2 and interferon-gamma production. Consistent with these data, Akiyoshi et al (2006) [18] showed that treatment with a 5-HT 2A antagonist enhanced the survival of cardiac allograft in mice.…”
Section: -Ht and Adaptive Immunitymentioning
confidence: 71%
“…Inoue et al (2011) [17] showed that a 5-HT 2A agonist enhanced Concavalin-A induced activation whereas a 5-HT 2A antagonist blocked T-cell receptor mediated interleukin-2 and interferon-gamma production. Consistent with these data, Akiyoshi et al (2006) [18] showed that treatment with a 5-HT 2A antagonist enhanced the survival of cardiac allograft in mice.…”
Section: -Ht and Adaptive Immunitymentioning
confidence: 71%
“…Furthermore, the mRNA of 5-HT2A, HT 4 and HT 7 receptor could be produced in activated T cells [6]. Moreover, selective 5-HT2A receptor inhibitor, sarpogrelate, induced longer survival of cardiac allografts in mice [7].…”
Section: Introductionmentioning
confidence: 98%
“…Of these15 receptors, signaling via 5-HT2A receptor (5-HT2AR) is important for regulation of the modulation of mood and perception in the central nervous system and of vasoconstriction and platelets aggregation in the periphery [4]. Increasing body of evidence suggests that this bioactive amine and its 5-HT2AR, in addition to these described activities, might also contribute to the immune system [5][6][7][8]. Prior to the classification of 5-HT2 receptor subtype [9], there had been some reports indicating that 5-HT could be a potent stimulator in T cell activation [10][11][12][13] although it was unclear which subtype of receptor mediated this activity.…”
Section: Introductionmentioning
confidence: 98%
“…However, the role of 5-HT 2A receptors in inflammatory processes is unclear, with only a very few published and inconsistent reports. Some studies report that blockade of 5-HT 2A receptor function with the selective antagonist sarpogrelate can decrease expression of proinflammatory markers (Marconi et al, 2003;Akiyoshi et al, 2006), whereas others indicate that sarpogrelate can increase expression of proinflammatory markers (Ito et al, 2000). Cloëz-Tayarani et al (2003) have alleged that the 5-HT 2 receptor-specific agonist 1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane (DOI) represses interleukin (IL)-1␤ expression and production of tumor necrosis factor-␣ (TNF-␣) through 5-HT 2A receptor activation.…”
mentioning
confidence: 99%